Towards a knowledge society : new identities in emerging India - SinghaRoy, Debal K., 1957- (Cambridge : Cambridge University Press, 2014)
This book depicts the emergence of knowledge society across rural and urban spaces and among cross sections of social collectivities in India. It analyses the new economic momentum and socio-cultural milieu as set in motion with the emergence of this society. The ensuing impact on the pre-existing facets of social identity and marginality, and the processes of construction of new social identities therein are studied. This book delineates both the hope and despair, as produced with the arrival of the knowledge society, and identifies the scope and conditions of alternative choice and liberation for the people within the emerging socio-economic order of this society. Rich in empirical data, this monograph will interest students, researchers, teachers, policy planners and social activists.
Introduction : conceptualising knowledge society : critical dimensions and ideal image -- Critiquing and contextualising knowledge society -- Strategising for knowledge society in India : the shifting backdrops and emerging contexts -- Education for knowledge society in India -- Information and communication technologies for knowledge society -- Indian growth story : service and knowledge dynamics -- Education, ICTs and work : the divergent empirical reality -- knowledge society : work, workers and work relations -- knowledge society : culture, continuity and contradictions -- Conclusion : marginality, identity, fluidity and beyond.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Information society -- India; Knowledge economy -- India; Information technology -- Social aspects -- India